2014
DOI: 10.1186/2193-1801-3-711
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oryza sativa husk and Quercus phillyraeoides extracts for the in vitro and in vivo control of fungal rot disease of white yam (Dioscorea rotundata Poir)

Abstract: Tuber rot disease is a major constraint to white yam (Dioscorea rotundata) production, accounting for 50-60% of annual yield losses in Nigeria. The main method of control using synthetic fungicides is being discouraged due to human and environmental health hazards. The potential of Oryza sativa husk (OSH) and Quercus phillyraeoides (QP) extracts for the in vitro and in vivo control of six virulent rot-causing fungal pathogens, Lasiodiplodia theobromae, Aspergillus niger, Rhizoctonia solani, Penicillium oxalicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Robin) Berkhout , Penicillum feniculosum Thom, and P. ochrochloron Biourge has also been observed for methanolic extracts of Q. acutissima Carruth ., Q. macrocarpa Michx., and Q. robur L. bark, with MIC values ranging from 160 to 2000 µg·mL −1 [ 29 ]. Dania et al [ 30 ] found that Q. phillyreoides A. Gray bark aqueous extract, at a concentration of 3%, resulted in strong inhibition of mycelial growth (>77%) in in vitro tests against Rhizoctonia solani J.G.…”
Section: Discussionmentioning
confidence: 99%
“…Robin) Berkhout , Penicillum feniculosum Thom, and P. ochrochloron Biourge has also been observed for methanolic extracts of Q. acutissima Carruth ., Q. macrocarpa Michx., and Q. robur L. bark, with MIC values ranging from 160 to 2000 µg·mL −1 [ 29 ]. Dania et al [ 30 ] found that Q. phillyreoides A. Gray bark aqueous extract, at a concentration of 3%, resulted in strong inhibition of mycelial growth (>77%) in in vitro tests against Rhizoctonia solani J.G.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of inoculum was done as previously described in the pathogenicity experiment. Trichoderma species were applied as soil drench at 4 ml per planting hole at a concentration adjusted to 2.5 × 10 8 using an hemocytometer (Dania et al, 2014) before sowing. Seven and half grammes of isolate SR 06-ramified wheat seeds were used to inoculate the soil around the base of healthy cowpea plants at two weeks after sowing while control plants were not inoculated with the pathogen.…”
Section: Evaluation Of Trichoderma Species For the Management Of Stem...mentioning
confidence: 99%
“…Detailed structural features of each isolate were observed using a compound microscope and identification was done following standard manual of fungi (Barnett and Hunter, 1998). Inoculum concentration was quantified and adjusted to 2 x 10 4 using the method of Dania et al (2014).…”
Section: Field Sampling and Fungal Isolationmentioning
confidence: 99%
“…Inoculated treatments were incubated in aerated crates at 28±2 0 C for four months. Percent rot inhibition was calculated according to Dania et al (2014).…”
Section: Evaluation Of Trichoderma Species For In Vivo Tuber Rot Treamentioning
confidence: 99%